Postcolonial Melancholy? The Shifted Reception of Ahmadou Kourouma's Monnè, outrages et défis (1990) - (:unkn) unknown (My University, 2010)
The notion of “postcolonial melancholia” allows for a description of the way in which the French literary establishment (publishing houses, reviews, literary prizes, critical reception) considered a book about the colonial period, as suggested by the sociological analysis of the conditions of production and reception of Monnè, outrages et défis, a novel by Ivorian author Ahmadou Kourouma. While the writer wanted to denounce colonialism with this book, he was disappointed by the way in which it was initially received and subsequently modified the direction of his writing by tackling more contemporary topics. By analyzing the universe of possible literary representations of colonialism by novelists from francophone sub-Saharan Africa from the 1950s until 1990, this article makes visible the set of structural forces that have impacted Kourouma’s original project. The dependency of francophone African literature published in France upon a French literary field that no longer recognizes the concept of “engagée” literature thus becomes internalized and transformed by the writer, resulting in the elaboration of an original literary form.
Keywords: African Research